Measurement and evaluation of specific absorption rate and temperature elevation caused by an artificial hip joint during MRI scanning - Youngseob Seo (Nature Portfolio, 2021)
Abstract A primary safety concern in a magnetic resonance imaging environment is heating of metallic implants by absorbing radiofrequency (RF) energy during MRI scanning. Experimental measurement in conjunction with computational modeling was used to evaluate the risk of biological tissue injury from the RF heating of artificial hip joints by obtaining both specific absorption rate (SAR) and temperature elevation at 1.5 T and 3 T MRI systems. Simulation result showed that high SAR and high temperature appeared near both head and tail sections of the artificial hip joints. For five different 1.5 T and 3 T MRI systems, measured temperature location showed that high temperature rises occurred near both head and tail regions of the metallic hip joints. Measured SAR value of 24.6 W/kg and the high temperature rise (= 4.22 °C) occurred in the tail region of the hip joint at 1.5 T, which was higher than the limits for temperature required by the international electrotechnical commission 60601-2-33. We have demonstrated the feasibility of evaluating RF heating of metallic hip joints during MRI scans.